Does the performance of global commodities exhibit co-movement and long-run relationship with the palm oil companies? - Izaan Jamil; Mori Kogid; Thien Sang Lim; Nelson Lajuni (ResearchGate, 2024)
While numerous papers investigate on the co-movement of global commodities and stock indices, this paper extends to previous papers by focusing on the individual stock price of palm oil companies namely Sime Darby Plantation, Wilmar International, and Astra Agri Lestari. Weekly data spanning from January 2018 to September 2023 was selected and Autoregressive Distributed Lags (ARDL) model employed to demonstrate the possible comovement and long-run relationship. Empirical results provide sufficient evidence of comovement between global commodities with Sime Darby Plantation and Astra Agri Lestari in the long-run. This will allow fund managers, individual investors, and stock traders to make investment decisions, trading strategies, and portfolio management based on the global commodity markets.